Evaluasi Beban Kerja Pegawai dan Dampaknya terhadap Efektivitas Pelayanan Publik - Nur Arista Dotulong; Ismet Sulila; Yacob Noho Nani (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study analyzes the influence of workload on the effectiveness of public service delivery at the Gorontalo City Land Office. The research is motivated by concerns that increasing service volume, organizational constraints, and uneven digital readiness have created significant workload imbalances, potentially hindering optimal service performance. The study focuses on examining how excessive workload, limited organizational support, and partial digitalization collectively affect the timeliness, accuracy, responsiveness, and overall quality of land administration services. Employing a qualitative descriptive-evaluative design, data were collected through in-depth interviews, observation, and document analysis, and subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings demonstrate that employees experience substantial role overload, time pressure, and dual workloads due to the simultaneous execution of manual and digital tasks. These conditions directly correlate with delayed service processes, increased administrative errors, weakened coordination, and declining public satisfaction. The study concludes that workload management is a critical determinant of public service effectiveness and a fundamental element of sustainable bureaucratic reform. The findings imply the need for data-driven workload evaluation, strengthened human resource planning, digital literacy enhancement, and improved technological infrastructure to ensure the provision of responsive, efficient, and citizen-centered public service.